Effects of Modified Digestion Schemes on the Identification of Proteins from Complex Mixtures - Klammer, Aaron A. (2006)
In shotgun proteomics, a complex protein mixture is digested to peptides, separated and identified by microcapillary liquid chromatography followed by tandem mass spectrometry (LC-MS-MS). In this technology, complete protein digestion is often assumed. We show that, to the contrary, modifications to a standard digestion protocol demonstrate large, reproducible improvements in protein identification, a result consistent with digestion being a limiting factor in the efficiency of protein identification.